The effect of radial swirl generator on reducing emissions from bio-fuel burner system - Mohamad Shaiful Ashrul, Ishak; Mohammad Nazri, Mohd Jaafar; A. Eldrainy, Yehia (Canadian Center of Science and Education, 2011)
Link to publisher's homepage at http://www.ccsenet.org/